Bottle feeding, increased overjet and Class 2 primary canine relationship: is there any association? - Nadia Salem Abdel Jabbar; Ana Beatriz Miguel Bueno; Patrícia Elaine da Silva; Helio Scavone-Junior; Rívea Inês Ferreira (Sociedade Brasileira de Pesquisa Odontológica, 2011)
The aim of this study was to investigate the association between bottle feeding and prevalence rates of increased overjet and Class 2 primary canine relationship. The sample consisted of 911 children (461 boys, 450 girls) aged 3 (13.9%), 4 (40.8%), 5 (34%) and 6 (11.3%) years, with complete primary dentition. Information about nutritive and nonnutritive (pacifier and/or digit) sucking habits was collected through questionnaires. Three calibrated dentists (κ: 0.9-1.0 and Rs > 0.90) performed the clinical assessments. The children were divided into four groups: G1 - not bottle-fed; G2 - exclusively bottle-fed; G3 - breast- and bottle-fed, bottle feeding ceased before 3 years of age; and G4 - breast- and bottle-fed, bottle feeding ceased between 3 and 4 years of age. Associations between nutritive and nonnutritive sucking behaviors and the malocclusions studied were analyzed by multiple binary logistic regression (α= 0.05). The frequencies of increased overjet were: 25.3% (G1), 38.8% (G2), 39.2% (G3) and 47.8% (G4). The percentages of Class 2 canine relationship were: 27.9% (G1), 48.8% (G2), 43.4% (G3) and 43% (G4). No significant effect of bottle feeding was found. The chances of diagnosing increased overjet (O.R. = 4.42, p < 0.001) and Class 2 canine relationship (O.R. = 4.02, p < 0.001) were greater for children with pacifier and/or digit-sucking habits, compared to those without a history of nonnutritive sucking behavior. It may be suggested that bottle feeding alone is not directly associated with higher prevalence rates of increased overjet and Class 2 canine relationship in the primary dentition.